2005
DOI: 10.1182/blood-2004-09-3428
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced activation of the p53 tumor suppressor in leukemia cells and normal lymphocytes requires mitochondrial activity and reactive oxygen species

Abstract: The p53 system is highly stress sensitive and integrates diverse intracellular signals in a complex and poorly defined manner. We report on the high dependence of stress-induced p53 activation on mitochondrial activity. Down-regulation of mitochondrial transmembrane potential (MTMP) by inhibitors of electron transport (rotenone, thenoyltrifluoroacetone (TTFA)) and adenosine triphosphate (ATP) synthesis (oligomycin) prevented stress-induced p53 protein accumulation and abrogated p53-dependent apoptosis in a wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
37
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 66 publications
7
37
1
Order By: Relevance
“…Previous evidence suggests that mitochondrial ETC could play a role in stress-induced activation of p53 (13)(14)(15)(16). However, in the present study we found that the inhibition of mitochondrial ETC does not necessarily generate p53-activating signals.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previous evidence suggests that mitochondrial ETC could play a role in stress-induced activation of p53 (13)(14)(15)(16). However, in the present study we found that the inhibition of mitochondrial ETC does not necessarily generate p53-activating signals.…”
Section: Discussioncontrasting
confidence: 55%
“…However, the role of mitochondrial ETC activity in the induction of p53 response remains ambiguous. It was suggested that mitochondrial activity could be required for the stress-induced activation of p53, as inhibitors of complexes I and V mitigate the response to etoposide treatment (14) and inhibitors of complex III interfere with the activation of p53 after treatment with cisplatin (15). On the other hand, it was noticed that certain ETC inhibitors produce a cell senescence phenotype associated with a modest activation of p53, leading to the suggestion that the reduced mitochondrial membrane potential (MMP) could initiate the p53 response (16).…”
mentioning
confidence: 99%
“…Also, generation of reactive oxygen species (ROS) and resulting oxidative stress often accompanies disturbed DNA integrity in cells exposed to topoisomerase inhibitors [28,29] and to this end our data indicating significantly elevated levels of oxidative stress in treated cells agree with this scenario. ROS may activate an entire array of stress signaling mediators including stress kinases p38 and SAPK/JNK [30,31].…”
Section: Discussionsupporting
confidence: 81%
“…Ϫ/Ϫ cells, as expected (16); however, this treatment did not normalize p53 levels in Redd1 Ϫ/Ϫ cells and instead may have further increased the relative difference in p53 levels between Redd1 Ϫ/Ϫ and wild-type cells (Fig. 4C).…”
Section: Increased Dna Damage Sensitivity Of Redd1mentioning
confidence: 54%